The Effectiveness Of Relaxation Methods And Music On A Gentle Labor Experience - Hamdia Anas; Sarjani Linggi Allo; Kiki Uniatri Thalib; Karnely Karnely; Agnes Batmomolin; Cakrawati R Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Gentle labor (Birth) is a birth approach that emphasizes comfort, calm, and a positive experience for both mother and baby. Relaxation and music therapy are non-pharmacological interventions that can help mothers reduce anxiety and pain during labor. This study aims to analyze the effectiveness of relaxation and music methods on the experience of gentle labor in mothers. The study used a quasi-experimental design with a pretest - posttest approach. The study sample was 50 mothers who gave birth, selected using a purposive sampling technique. The intervention, in the form of relaxation exercises and music therapy, was given during the active labor phase. Data were collected using a childbirth experience questionnaire and a pain scale. Data analysis used paired t- test and chi-square tests. The results showed that mothers who received relaxation and music interventions had a higher level of labor comfort and lower pain intensity compared to before the intervention (p = 0.015). It was concluded that relaxation and music methods are effective in supporting a gentle labor experience.